CHILD COUNSELING WITH JAVANESE LANGUAGE ROLE PLAY METHOD TO BUILD EARLY CHILDREN CHARACTERS - Hidayati, Richma; Syafitri, Dewi; Nindya, Nazulla Niftira; Izzah, Nailatul (Universitas Muria Kudus, 2017)
Character of the nation today is quite alarming so as to make the government a loss and several times changed the curriculum to be able to shape the character of the nation in accordance with Indonesian culture. So should the stress is learning in cultural values, not just focusing on modernization by requiring students to master a foreign language, English for example. By studying the local language does not mean students will be retarded or even not able to follow the development of the era. Precisely with the generation of the nation early on if it was taught the habit of using the local language then the child will be proud to be able to introduce the local language to the outside world through the modernization of the moment. Additionally, when children understand very well about the local wisdom then the child will have a character in accordance with Indonesian culture. Role playing is a way of mastery learning materials through the development of imagination and appreciation of students. Development of imagination and appreciation of the students is done with playing the character of living or inanimate. Counseling children with role-play techniques in this program focuses using the Java language manners. Java language is divided into three levels, namely language ngoko (rough), madya (regular) and krama (smooth). In this language levels, its use varies according to who they are talking to an opponent. Everyday, ngoko used to talk with peers or younger, madya used to talk to the person who is quite formal, and krama used to talk with people who are respected or older. Therefore, the Java language has ethical good language to use and reflect the characteristics of the indigenous culture of Indonesia as a nation east. Keyword : Child Counseling, Javenese Role Play, Character Early Childhood